Hubungan antara Fanatik dengan Agresi pada Penggemar EXO (Indo-MathEdu Intellectuals Journal, 2024)
South Korean culture, especially K-pop, has achieved great global popularity. However, this popularity has also brought about a new phenomenon, namely fan culture which leads to intense fanaticism. This fanaticism often leads to aggressive behavior that occurs between competing fans. The approach used is quantitative research. The type of research used is quantitative correlational. The population in this study were EXO (EXO-L) Lombok fans, totaling 198 people. The technique used was purposive sampling and used a Krejcie table to determine the number of samples of 115 samples. Based on the findings of the research conducted, it can be said that there is a weak but significant positive correlation in the bigotry variable and the aggression variable with a correlation coefficient (R) value of 0.287 (indicating the same direction). There is a relationship between fanaticism and aggression in EXO fans with the result p = 0.002 (with p < 0.01). These findings indicate that the higher the fanaticism shown by a fan, the higher the aggression towards the music group EXO and vice versa, the lower the fanaticism, the lower the aggression too. Advice for EXO fans to support idols with a positive attitude by respecting criticism, and using social media wisely can create a healthy and mutually supportive environment, which not only strengthens the relationship between idols and fans but also provides a positive example for other fans around the world